Das archäologische Museum „Berestje“. Die Geschichte der Musealisierung der archäologischen Stätte und die aktuelle Museumsentwicklung - Nekljudova, Tatjana; Baškov, Alexander (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2018)
The Berestye Archaeological Museum, a branch of the Brest Museum of Regional Studies (Brest, Republic of Belarus‘), is the only museum in Europe where an archaeological site with perfectly preserved 13th-century wooden buildings of an East Slavic town are exhibited. The discovery of the medieval town of Berestye was the result of large-scale excavations carried out in 1969–1981 and in 1988 under the guidance of Professor Piotr Lysenko. The characteristics of the wet cultural layer made it possible to preserve more than 220 wooden buildings and more than 43,000 objects of organic and inorganic origin. The long-term process of preserving wooden constructions was the first experience in the conservation and museumisation of such objects in the field.
Keywords: medieval Brest; archaeological site; archaeological museum; preservation; museumisation